2022
DOI: 10.1007/s12519-022-00655-w
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation in childhood: past, present, and future

Abstract: Background Fecal microbiota transplantation (FMT) has been well described in the treatment of pediatric diseases; however, the latest updates regarding its use in children are unclear and the concepts involved need to be revisited. Data sources We performed advanced searches in the MEDLINE, EMBASE, and Cochrane databases using the keywords “Fecal microbiota transplantation OR Fecal microbiota transfer” in the [Title/Abstract] to identify relevant articles published in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Fecal microbiota transplantation (FMT) is an effective approach to restoring the diversity and structure of the microbiota by transferring healthy gut microbiota to recipients. Extensive research has been conducted on FMT for various clinical disorders associated with the microbiome, in both adult [ 107 ] and pediatric populations [ 108 ].…”
Section: Microbiota Modulatory Therapies In Ckd Patientsmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) is an effective approach to restoring the diversity and structure of the microbiota by transferring healthy gut microbiota to recipients. Extensive research has been conducted on FMT for various clinical disorders associated with the microbiome, in both adult [ 107 ] and pediatric populations [ 108 ].…”
Section: Microbiota Modulatory Therapies In Ckd Patientsmentioning
confidence: 99%
“…Currently, clostridium difficile infection and recurrent clostridium difficile infection are considered to be the most appropriate indications for FMT in children. Moreover, FMT has also shown promising therapeutic effects in other pediatric diseases, including inflammatory bowel disease, irritable bowel syndrome, functional constipation, non-alcoholic fatty liver disease, ASD and diabetes ( 11 ). Although FMT has shown promise in treating various pediatric conditions, it remains under research and is not yet approved by clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A review in the Special Issue [14] showed that certain prebiotic-rich diets, such as resveratrol and garlic oil, have demonstrated protective efficacy against CKD in children [15]. In addition, fecal microbiota transplantation [16] and colon dialysis [17] have been shown to be effective in restoring the diversity and structure of intestinal microbiota in children with kidney disease.…”
mentioning
confidence: 99%